2019
DOI: 10.1042/bsr20192779
|View full text |Cite
|
Sign up to set email alerts
|

CircZFR serves as a prognostic marker to promote bladder cancer progression by regulating miR-377/ZEB2 signaling

Abstract: Circular RNAs (circRNAs) have been identified as crucial regulators of gene expression in human cancer biology. CircZFR is a novel identified circRNA and its effect in bladder cancer remains unclearly. In the present study, we aimed to investigate the role of circZFR in the progression of bladder cancer. First, we demonstrated that the expression of circZFR was higher in bladder cancer tissues and cells compared with adjacent non-tumor tissues and normal bladder epithelial cells. And higher circZFR levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…CircRNAs could bind to miRNAs and function as miR-NAs sponges [20]. Accumulating articles have reported the downstream miRNAs of circ_0072083 in diverse cancers [25][26][27]. Herein, miR-545-3p was verified as a target of circ_0072083 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 94%
“…CircRNAs could bind to miRNAs and function as miR-NAs sponges [20]. Accumulating articles have reported the downstream miRNAs of circ_0072083 in diverse cancers [25][26][27]. Herein, miR-545-3p was verified as a target of circ_0072083 in NSCLC cells.…”
Section: Discussionmentioning
confidence: 94%
“…Further analysis showed that high levels of these circRNAs are closely related to the clinicopathological stage of BC, which describes the tumor status, including the tumor size, presence of local and distant metastasis, and tumor pathological grade, and affect the survival of BC patients. [27][28][29][30][31][32][33][34] Regarding tumor tissue classifications, the levels of circRNAs, including circ-BPTF, circTFRC, circZFR, circPTK2, and circASXL1, were found to be significantly higher in low-grade BC tissues than in high-grade BC tissues. 27,28,30,32,33 Regarding the pathological TNM stage, circRNAs, including circTFRC, circZFR, circPRMT5, circPTK2, circASXL1 and circCASC15, were positively correlated with the T stage when patients were stratified into Ta-1 and T2-4 subgroups.…”
Section: Relationships Between Circrnas and Clinicopathological Charamentioning
confidence: 99%
“…[27][28][29][30][31][32][33][34] Regarding tumor tissue classifications, the levels of circRNAs, including circ-BPTF, circTFRC, circZFR, circPTK2, and circASXL1, were found to be significantly higher in low-grade BC tissues than in high-grade BC tissues. 27,28,30,32,33 Regarding the pathological TNM stage, circRNAs, including circTFRC, circZFR, circPRMT5, circPTK2, circASXL1 and circCASC15, were positively correlated with the T stage when patients were stratified into Ta-1 and T2-4 subgroups. 28,[30][31][32][33][34] Additionally, circTFRC, circZFR, circPRMT5, circPTK2 and circASXL1 were found to be closely related to lymph node status: BC patients with lymph node metastasis tended to have higher levels of these circRNAs.…”
Section: Relationships Between Circrnas and Clinicopathological Charamentioning
confidence: 99%
See 2 more Smart Citations